2019
DOI: 10.1186/s12891-019-2825-4
|View full text |Cite
|
Sign up to set email alerts
|

The expression of P16 and S100 associated with elastin degradation and fibrosis of the Ligamentum Flavum hypertrophy

Abstract: BackgroundOne of the characteristics of lumbar spinal stenosis (LSS) is elastin degradation and fibrosis in the ligamentum flavum (LF). However, the biochemical factors that cause these histologic changes is unclear. P16 and S100 participate in scar formation and collagen development in wound healing and fibrosis diseases. In this study, we investigate the association between P16 and S100 expression and the fibrosis of the hypertrophic LF in LSS.MethodsThe LF specimens were surgically obtained from 30 patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…In our previous study, we used imaging and histological methods to grade the degree of LF elastin fibrosis, and an immunohistochemical method was used to detect the expression of P16 and S100 in ventral and dorsal LF. We found that the expression of P16 may be related to LF hypertrophy [8].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…In our previous study, we used imaging and histological methods to grade the degree of LF elastin fibrosis, and an immunohistochemical method was used to detect the expression of P16 and S100 in ventral and dorsal LF. We found that the expression of P16 may be related to LF hypertrophy [8].…”
Section: Introductionmentioning
confidence: 65%
“…This may be due to LF being subjected to more stress from changes in living habits in recent years and possibly related to race [10]. In the previous study, we measured the absolute and relative thickness of LF and found that the thickness of LF in DLSS group and SLSS group was significantly higher than that in LDH group [8]. In this study, we further investigated the correlation between the thickness of LF and the expression of P16 and S100.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The measurement method of LF was done as in our previous study [8]. Relative thickness of LF (RT) was calculated as the percentage of the thickness of LF to the oblique diameter of lumbar spinal canal.…”
Section: Mri Measurementmentioning
confidence: 99%
“…The measurement method of LF was done as in our previous study [8]. We consider the ligamentum The average of three independent measurements of three surgeons were taken to determine the relative thickness of a single sample.…”
Section: Mri Measurementmentioning
confidence: 99%